Two-Tiered Network Design Architecture for Collision Avoidance Protocol in Wireless Sensor Networks - Widyasmoro, Widyasmoro (Journal of Electrical Technology UMY, 2018)
Collision avoidance multiple access plays a significant role in WirelessSensor Networks (WSN) as there may have a huge number of nodes in a network.Therefore, it has big chance to conflict when they want to send a packet to the server atthe same time. In our work, we focus on the sensor networks with two-tier network designarchitecture that composed of simple function nodes and presented performance analysisof the proposed collision avoidance multiple access protocol for Wireless SensorNetworks, with emphasis on the contention process exercising in each contention subframe.Then we also examine the efficiency of the overall system based on the simulationresults. The results shows that using different parameter of n, m, and k then the successfulprobability tends to increase, however after certain value of n, the successful probabilitywill decrease. Regarding the overall system efficiency, Esys, in order to get the optimumvalue of system efficiency, we have to maximize Î±. It is obvious that the bigger value of Î²will produce bigger value of Î±. That is mean a shorter contention sub-frame leads to abetter efficiency of the systems, if Lr (average length of transmission sub-frame) is fixed.